A transdisciplinary dual degree curriculum yields novel and successful learning outcomes: early lessons from training physicianeers - Wells, Gregg B.; Baxter, Douglas A.; Day, Leslie J.; Boone, Timothy B.; Moreno, Michael R.; Gibson, Jeremy L.; Peterson, Thomas V.; Martinez-Moczygemba, Margarita; Greene, Ericka P.; Sears, Nicholas; Paolini, Michael A.; Pettigrew, Roderic I. (Frontiers in Medicine, 2025)
The evolving needs in healthcare education and delivery have led to diverse MD-based dual degree programs offering trainees broader experiences and credential-based credibility after graduation. Medical schools typically implement multidisciplinary or interdisciplinary dual degree training with designs that separate the contributing disciplines chronologically and experientially. As a result, these designs fail to maximize the cohesive learning environment and outcomes possible with a transdisciplinary dual degree design, which integrates the contributing disciplines chronologically, experientially, and conceptually. Though rare, transdisciplinary dual degrees promise transformative educational outcomes and discipline convergence by dissolving traditional discipline boundaries and fostering a new learning environment and professional identity. Therefore, we hypothesize that a transdisciplinary dual degree curriculum yields novel—and potentially better—learning outcomes. ENMED, a transdisciplinary dual degree program collaboratively developed, sponsored, and implemented by Texas A&M University and Houston Methodist Hospital, is testing this hypothesis by training “physicianeers.” This new type of healthcare professional trains simultaneously for the MD and Master of Engineering degrees, thereby integrating medical and engineering expertise to advance health system innovations. Supporting the hypothesis, ENMED’s early experiences suggest its transdisciplinary dual-degree model leads physicianeer trainees to novel perspectives with the potential to transform healthcare systemically.